You can draw cartoon animals : a simple step-by-step drawing guide - Hart, Christopher (Irvine, CA : Walter Foster, 2009)
Provides step-by-step instructions for drawing eighty cartoon animals, including leopards, rats, bears, birds, and more.
"Ages 6+"--Cover p. [4].
"Draw 80 animals!"--Cover.
5.1
K-3.
K-3
Keywords: Animals in art -- Juvenile literature; Cartooning -- Technique -- Juvenile literature; Animals in art; Cartooning -- Technique; Animals in art; Cartooning -- Technique